History in V.S.Naipaul's Fiction - TOUZANI FATIMA ZAHRA (Faculté des Lettres et Sciences Humaines, Béni Mellal - Doctorat ou Doctorat National, 2022)
This thesis deploys the postcolonial theory to investigate the problematic of history in V. S. Naipaul’s novels. It also relies on history books to compare historical facts to Naipaul’s plots, make inferences and draw conclusions about history. Naipaul’s inordinate representation of individual, collective and universal history in fiction conveys an ardent interest in underlining the depth of postcolonial identity crisis. Naipaul reweaves his individual history to suit fiction because his transmission of his own experiences does not involve distortion, but reformulation. He represents Trinidad’s collective history in an inclusive way as he reshapes the island’s history, reconstructs it and fictionalizes it. Storytelling renders history more accurate as it concatenates historical events and homogenizes their idiosyncrasies. He finally varies his depiction of universal history from reconstruction, rectification, interpretation to allusion. Reconstructing past events, foreshadowing, criticizing, recollecting, filling in the blanks and suppressing are his techniques to present his understanding and vision of world history. Naipaul reduces individual, collective and universal history to a simple story that is close to truth. Naipaul’s portrayal of home, exile, displacement and alienation in the novels that fictionalize his individual history display a kind of identity vulnerability which engenders fragility and discloses a drastic need of belonging and an inability to identify with the metropolitan tradition. His portrayal of Amerindian, Hindu, Afro-Trinidadian and Euro- Trinidadian festivals feature a variety of ethnicities and bear traces of untold histories and evoke all the elements that have contributed to shape a distinguished Trinidadian identity. His representation of racialization, hybridity, mimicry and ambivalence in the novels that fictionalize world history recalls the oppression of the colonized, indicates that universal history is meant to highlight the detrimental effect of colonialism on the postcolonial hybrids’ conception of identity since it recalls the torture of African and Indian Diaspora. Far from being exhaustive, this dissertation opens an avenue of research into history in Naipaul’s fiction in particular and history in postcolonial fiction in general.
Keywords: postcolonial theory; history; V. S. Naipaul; novels; representation; identity crisis; storytelling; reconstruction; universal history; identity vulnerability; racialization; colonialism; Littérature; Études Postcoloniales